TAKSONOMI MAKANAN DAN MINUMAN DALAM BAHASA INGGRIS DAN BAHASA TONDANO (SUATU ANALISIS KONTRASTIF) - Umboh, Eklesia Saulin; Lotulung, Donald R.; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â This research is entitled â€œTaxonomy of Food and Beverage in English and Tondano Language (A Contrastive Analysis)â€. The objectives of this research are to identify, classify and describe the taxonomy of food and beverage, the way food and beverage are made and the basic ingredients of food and beverage in English and Tondano Language and to find out the similarities and differences in both languages. The data of food and beverage in English were collected from the text books, articles, and the website, while in Tondano Language were collected from informants and also by taking picture of foods and beverages in some wedding party, sorrow ceremony, restaurant, and traditional market. The data about foods in English and Tondano language that have been collected then identified, classified, and analyzed by using the theory of Frisch in Hickerson and the theory of Foley. Then, the data of both languages were contrasted by using Ladoâ€™s theory. The results of this research showed that in English and Tondano language, there are similarities in the food categories namely solid foods and beverages in English, and in Tondano language namely solid foods, and beverages. In English there are six kinds of solid food, such as meat, bread, fruits, vegetables, fish and sea food, but in Tondano language has five kinds of solid food, such as meat, fruits, vegetables, fish and rice. English and Tondano language has the same kinds of drinks, such as alcoholic and non-alcoholic drink. The way of food and beverage in English are made: namely baking, grilling, sauteing, boiling, steaming, blending and squeeze, while in Tondano language it is tapan/panggang â€œgrillingâ€, tinumis/tumis â€œsauteingâ€, ginoreng/goreng â€œfryingâ€, pinera/woku â€œfrying/grillingâ€, kinukus/kukus â€œsteamingâ€, tinunu/bakar â€œbakingâ€, and rinubus/rebus â€œboilingâ€. Food and beverage based on the basic ingredients in English are meat, fish, wheat, flour, fruits, vegetables, milk, coffee, and herbal plants, while in Tondano language are daging â€œmeatâ€, ikan â€œfishâ€, sayur-sayuran â€œvegetablesâ€, buah-buahan â€œfruitsâ€, susu â€œmilkâ€, tepung â€œflourâ€, umbi-umbian â€œtubersâ€, beras â€œriceâ€, kopi â€œcoffeeâ€, pohon â€œtreeâ€ dan daun â€œleafâ€.Keywords: Taxonomy of Food and Beverage, English and Tondano Language, Contrastive Analysis